Epidemic cholera in Kakuma Refugee Camp, Kenya, 2009: the importance of sanitation and soap - Mahamud, Abdirahman Sheikh; Ahmed, Jamal A; Nyoka, Raymond; Auko, Erick; Kahi, Vincet; Ndirangu, James; Nguhi, Margaret; Burton, John Wagacha; Muhindo, Bosco Z; Breiman, Robert F; Eidex, Rachel B. (Journal of infection in developing countries, 2012)
Introduction: Cholera remains a major public health problem that causes substantial morbidity and mortality in displaced populations due to inadequate or unprotected water supplies, poor sanitation and hygiene, overcrowding, and limited resources. A cholera outbreak with 224 cases and four deaths occurred in Kakuma Refugee Camp in Kenya from September to December 2009. Methodology: We conducted a case-control study to characterize the epidemiology of the outbreak. Cases were identified by reviewing the hospital registry for patients meeting the World Health Organization (WHO) case definition for cholera. For each case a matched control was selected. A questionnaire focusing on potential risk factors was administered to cases and controls. Results: From 18 September to 15 December 2009, a total of 224 cases were identified and were hospitalised at Kakuma IRC hospital.  Three refugees and one Kenyan national died of cholera. V. cholerae O1, serotype Inaba was isolated in 44 (42%) out of 104 stool specimens collected. A total of 93 cases and 93 matched controls were enrolled in the study. In a multivariate model, washing hands with soap was protective against cholera (adjusted odds ratio [AOR] =0.25[0.09-0.71]; p < 0.01), while presence of dirty water storage containers was a risk factor (AOR=4.39[1.12-17.14]; p=0.03). Conclusion:  Provision of soap, along with education on hand hygiene and cleaning water storage containers, may be an affordable intervention to prevent cholera.